A Study on Early Childhood Teachers and Pre-service Teachers’ Belief, Confidence, and Using Technology in Teaching Mathematics for Early Childhood Students - Yimchang, Anongnart; Chaiwanna, Suchanard; Philuek, Wudhijaya (International Journal of Integrated Education and Development, 2018)
Teaching Mathematics to children in early year is essential to early childhood students. The purposes of this study were aimed: to investigated and to compared the Early Childhood teachers and pre-service teachers’ belief, confidence, and use of technology in teaching Mathematics for Early Childhood student. This data collection used survey method from 67 Early Childhood teachers from Nakhon Sawan Primary Educational Service Area Office which came from the sample technique and 70 of 4th year Early Childhood pre-service teachers from Nakhon Sawan Rajabhat University, Nakon Sawan Province, Thailand which came from purposive technique. The results shows that the teachers’ belief about Early Childhood Students and Mathematics” and “Teachers confidence in helping Early Childhood Students learn Mathematics” and “Teachers’ Confidence in Their Personal Mathematics Abilities” between in-service and pre-service teachers were different with .05 level of statistical significant where pre-service teacher have higher belief than in-service teachers. However, in “Fear in in their personal Mathematics abilities” it shows that in-service teacher have higher belief than pre-service teachers with different with .05 level of statistical significant. This research will be benefit to develop the training program to both in-service and pre-service teachers in developing confident, belief, and using of technology in teaching Mathematics to Early Childhood Students.